Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 46424 by maxmathsup by imad last updated on 25/Oct/18

let f(x)=(e^(−x) /(x^2 +4))  1) calculate f^((n)) (x) and f^((n)) (0)  2) developp f at integr serie .

letf(x)=exx2+41)calculatef(n)(x)andf(n)(0)2)developpfatintegrserie.

Commented by maxmathsup by imad last updated on 27/Oct/18

1) we have f(x)=(e^(−x) /((x−2i)(x+2i))) =(1/(4i))e^(−x) { (1/(x−2i)) −(1/(x+2i))}  =(1/(4i)){(e^(−x) /(x−2i)) −(e^(−x) /(x+2i))} ⇒f^((n)) (x)=(1/(4i)){ ((e^(−x) /(x−2i)))^((n))  −((e^(−x) /(x+2i)))^((n)) }  leibniz formulae give   ((e^(−x) /(x−2i)))^((n))  =Σ_(k=0) ^n  C_n ^k  ((1/(x−2i)))^((k))  (e^(−x) )^((n−k))   =Σ_(k=0) ^n  C_n ^k  (((−1)^k k!)/((x−2i)^(k+1) )) (−1)^(n−k)  e^(−x )   also we have   ((e^(−x) /(x+2i)))^((n))  =Σ_(k=0) ^n  C_n ^k   (((−1)^k  k!)/((x+2i)^(k+1) )) (−1)^(n−k)  e^(−x)  ⇒  f^((n)) (x)=(1/(4i)) Σ_(k=0) ^n  (−1)^n  C_n ^k  k!{(1/((x−2i)^(k+1) )) −(1/((x+2i)^(k+1) ))}e^(−x)   =(1/(4i)) Σ_(k=0) ^n  (−1)^n   ((n!)/((n−k)!)) (((x+2i)^(k+1) −(x−2i)^(k+1) )/((x^2  +4)^(k+1) )) e^(−x)

1)wehavef(x)=ex(x2i)(x+2i)=14iex{1x2i1x+2i}=14i{exx2iexx+2i}f(n)(x)=14i{(exx2i)(n)(exx+2i)(n)}leibnizformulaegive(exx2i)(n)=k=0nCnk(1x2i)(k)(ex)(nk)=k=0nCnk(1)kk!(x2i)k+1(1)nkexalsowehave(exx+2i)(n)=k=0nCnk(1)kk!(x+2i)k+1(1)nkexf(n)(x)=14ik=0n(1)nCnkk!{1(x2i)k+11(x+2i)k+1}ex=14ik=0n(1)nn!(nk)!(x+2i)k+1(x2i)k+1(x2+4)k+1ex

Commented by maxmathsup by imad last updated on 27/Oct/18

x=0 ⇒f^((n)) (0) =(1/(4i)) Σ_(k=0) ^n (((−1)^n n!)/((n−k)!)) (((2i)^(k+1)  −(−2i)^(k+1) )/4^(k+1) )  =(1/(4i)) Σ_(k=0) ^n   (((−1)^n n!)/((n−k)!)) ((2i Im{(2i)^(k+1) })/4^(k+1) ) =(1/2) Σ_(k=0) ^n  (((−1)^n n!)/((n−k)!))  ((2^(k+1)  sin((((k+1)π)/2)))/2^(2k+2) )  = Σ_(k=0) ^n  (((−1)^n n!)/((n−k)!)) ((sin((((k+1)π)/2)))/2^(k+2) )

x=0f(n)(0)=14ik=0n(1)nn!(nk)!(2i)k+1(2i)k+14k+1=14ik=0n(1)nn!(nk)!2iIm{(2i)k+1}4k+1=12k=0n(1)nn!(nk)!2k+1sin((k+1)π2)22k+2=k=0n(1)nn!(nk)!sin((k+1)π2)2k+2

Commented by maxmathsup by imad last updated on 27/Oct/18

2) we have f(x) =Σ_(n=0) ^∞  ((f^((n)) (0))/(n!)) x^n  ⇒  f(x) =Σ_(n=0) ^∞  (−1)^n ( Σ_(k=0) ^n  (1/((n−k)!)) ((sin((((k+1)π)/2)))/2^(k+2) ))x^n  .

2)wehavef(x)=n=0f(n)(0)n!xnf(x)=n=0(1)n(k=0n1(nk)!sin((k+1)π2)2k+2)xn.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com